Biološki označevalci in njihova uporaba pri razvoju in zagotavljanju varnosti zdravil - Fic, Anja (Farmacevtski vestnik, 2013)
Biomarkers are biological indicators of health, disease or poisoning, and are now widely applicable in determining the etiology of the disease, pathophysiological, pharmacological, toxicological processes and diagnostics. In the process of research and development of new drugs we can use validated biomarkers to measure the effectiveness of therapy and predict the adverse effects of drugs. So biomarkers can increase the success rates in drug development. They can reduce the costs and shorten the drug development process, they can help in selecting the best drug candidates and they can predict efficacy and safety of the drugs and open the way for personalized medicine.
Keywords: biološki označevalci; farmakologija; klinična farmakologija; razvoj zdravil; security; toksikologija; varnost